(Un)Directed Reading, an interactive kiosk to encourage writing and reading - Olga Ng Ka Man, Sandra; Estadieu, Gerald; Farinha, Daniel (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
(Un)Directed Reading is an interactive installation (Edmonds, 2010) initially derived from the “Directed Reading” course, which all undergraduate students at the University must take during their final year. In this course, students are assigned different writing exercises and research assignments to open their creative and constructive minds in writing (EdwardsGroves, 2012; McVey, 2008). Every year, at the end of the course and after a selection process, a collection of stories is uploaded to a database of original stories. We then developed an open-source application to print a receipt ticket from a thermal printer with a randomly picked story every time a user pushes a button. An arcade game-style button is installed on a kiosk designed in collaboration with students and set on the university's campus (left photo). The printed receipt presents a short extract of one of the stories and a QR code that links to the full story decorated with illustrations. In a modern society where most of our interactions are audiovisual-based, young generations are less and less encouraged to read and even less to write. By offering a simple kiosk installation with short stories and graphical illustrations, we propose a new interactive interface that can easily engage passers-by to eventually stimulate their reading and creativity. By reading these stories, students, professors, staff, and visitors can be surprised by the talent of our students, as it stimulates students to write new pieces to be selected. The interactive kiosk was accessible to all for a period of 3 months with 23 stories during which we automatically collected some data to use in quantitative analysis. In this first run, we focused on data from the user's interactions such as story printed, story read, date and time. It allowed us to see the ratio between the printed receipt and the actual online reading of a story and more.

(Un)directed Reading: Selected Students' Work Directed Reading 2020/21 University of Saint Joseph, Macao, China - Olga Ng Ka Man, Sandra (University of Saint Joseph, 2023)
Keywords: Literature

Design Thinking Methodology and Text-To-Image Artificial Intelligence: A Case Study in the Context of Furniture Design Education - Caires, Carlos Sena; Estadieu, Gerald; Olga Ng Ka Man, Sandra (Perspectives on Design and Digital Communication IV: Research, Innovations and Best Practices, 2024)
The design thinking methodology is a problem-solving approach that involves empathising with end-users, (re)defining problems, brainstorming solutions creatively, and experimenting with prototypes and testing. It has been widely adopted in education to help students develop critical thinking, creativity, and problem-solving skills in design. On the other hand, text-to-image artificial intelligence is a method used to generate images from natural language descriptors (usually referred to as prompts). Design thinking methodology can teach students to think creatively and critically about real-world problems when applied in the classroom. In the context of design teaching at the University of Saint Joseph, Macao, students use the design thinking methodology to develop innovative proposals for furniture design solutions. Combining design thinking methodologies with text-to-image artificial intelligence can further enhance the learning experience by allowing students to generate visual representations of their ideas during the ideation phase. The authors developed a systematic approach to generate images for ideation on furniture design based on prompting text-to-image (PTI). The analysis related students’ results who applied the design thinking methodology without using AI tools and the results generated using a standard text-to-image programme. By combining both methods, teachers can help students develop critical thinking, creativity, and problem-solving skills, while also allowing them to generate visual representations in a different paradigm and, by so, being able to communicate their ideas with the most appropriate support for them.
Keywords: Artificial intelligence; Design thinking; Education quality; Furniture design education; Text-to-image prompt

Radial String Chimes: A Behavioural Driven Tangible Instrument Derived from Networked Music Performance Practices - Barbosa, Alvaro; Olga Ng Ka Man, Sandra; Estadieu, G (Ubimus 2023, 2023)
Research in ubiquitous networked music systems has unveiled the potential of behavioural-driven interaction interfaces as an effective model to cope with network communication delays in remote musical performances. Most of the techniques developed under these premises are based on digital music interfaces implemented on laptop computers or tablet devices, where a certain degree of gestural control comes as an added dimension. The purpose of this paper is to present an implementation of such type of interfaces in the form of a physical tangible musical instrument, contemplating multiple expressive possibilities. This is viable at the current stage of technological development thanks to leveraging 3D printing and laser cutting technologies for effective prototyping and testing of such a device. The paper seeks to demonstrate that this approach opens a wide range of possibilities for creating musical instruments with versatility and expressiveness beyond what is usually accomplished in traditional instruments. This implementation, entitled “Radial String Chimes,” is presented with its advantages, the challenges it faces, and the methods used to create it. Finally, the paper will offer suggestions for further developing such an instrument to unlock its potential.